The Calcitonin/Calcitonin Gene-Related Peptide Family in Invertebrate Deuterostomes - Sekiguchi, Toshio (Frontiers in Endocrinology, 2018)
Calcitonin (CT)/CT gene-related peptide (CGRP) family peptides (CT/CGRP family peptides) including CT, CGRP, adrenomedullin, amylin, and CT receptor-stimulating peptide have been identified from various vertebrates and perform a variety of important physiological functions. These peptides bind to two types of receptors including CT receptor (CTR) and CTR-like receptor (CLR). Receptor recognition of CT/CGRP family peptides is determined by the heterodimer between CTR/CLR and receptor activity-modifying protein (RAMP). Comparative studies of the CT/CGRP family have been exclusively performed in vertebrates from teleost fishes to mammals and strongly manifest that the CGRP family system containing peptides, their receptors, and RAMPs was derived from a common ancestor. In addition, CT/CGRP family peptides and their receptors are also identified and inferred from various invertebrate species. However, the evolutionary process of the CT/CGRP family from invertebrates to vertebrates remains enigmatic. In this review, I principally summarize the CT/CGRP family peptides and their receptors in invertebrate deuterostomes, highlighting the study of invertebrate chordates including ascidians and amphioxi. The CT/CGRP family peptide that shows similar molecular structure and function with that of vertebrate CT has been identified from ascidian, Ciona intestinalis. Amphioxus, Branchiostoma floridae also possessed three CT/CGRP family peptides, one CTR/CLR receptor, and three RAMP-like proteins. The molecular function of the receptor complex formed by amphioxus CTR/CLR and a RAMP-like protein was clarified. Moreover, CT/CGRP family peptides have been identified in the superphylum Ambulacraria, which is close to Chordata. Finally, this review provides potential hypotheses of the evolution of CGRP family peptides and their receptors from invertebrates to vertebrates.